Design Of Vibration Measurement System For Steel Frame Bridge Structure - Yoga Alif Kurnia Utama (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Transportation that is not supported by adequate road and bridge access will result in hampered aid to victims of natural disasters. Moreover, bridges that collapse due to natural disasters will cripple the region's economy. The importance of this bridge access requires a tool that can describe a bridge's resilience and strength. So if the strength of the bridge decrease, then corrective action will be taken immediately. In this research, a system will be created that can measure the bridge's strength from the vibration load received by the bridge. This system will be made using a vibration sensor, the ADXL335 accelerometer. This sensor will measure the vibration on a miniature bridge where the vibration is created using a DC motor which is weighted on one side of the rotor. This sensor will be read by a microcontroller with an Arduino type. This measurement will be compared with the Benetech GM63A type vibration meter. The results show that the measurement of this system produces a measurement error of 2.97%. From this, it can be known that the system is good as a vibration measurement tool on a real steel truss bridge.